2014
DOI: 10.1007/s12666-014-0445-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation, Compressive and Tensile Deformation Study of In-Situ Al–AlN Metal Matrix Composites

Abstract: In-situ formation of ceramic particulate as a reinforcement in Al matrix results in superior mechanical properties of synthesized Al based composites. Resulting composites are thermodynamically stable with clean particulates having strong bonding with matrix. In the present study, Al melt held at 700°C is nitrogenated using NH 4 Cl ? CaO as a nitriding precursor to form ultrafine AlN particulates in melt. Nanoindentation, tensile and compressive tests are conducted on the synthesized composite to evaluate its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The experiments have found that the prepared AlN/Al composites containing well distributed AlN nano-partciles produced by means of nitriding of Al-liquids exhibit improved mechanical performances. [2,[19][20][21] This topic deserves further investigation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The experiments have found that the prepared AlN/Al composites containing well distributed AlN nano-partciles produced by means of nitriding of Al-liquids exhibit improved mechanical performances. [2,[19][20][21] This topic deserves further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…The obtained information is helpful to understand the interaction between liquid Al to AlN particles, and further to enrich our understanding of heterogeneous nucleation, [5,6,16,52,53] as well as for AlN-containing composites [2,[19][20][21][22] and ceramic-metal welding. [27] V. CONCLUSIONS…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation